METHODS AND METHODS OF PARENTERAL NUTRITION IN POSTOPERATIVE CONDITIONS IN INFANTS - Xusniddinova Saida (New modern researchers: modern proposals and solutions, 2025)
This article discusses the methods and methods of parenteral nutrition in postoperative conditions in infants.